Diagnostic and prognostic value of calf circumference for sarcopenia in community-dwelling older adults - Alejandro Álvarez-Bustos; Jose Antonio Carnicero; Helio José Coelho-Junior; Riccardo Calvani; Francisco José García-García; Emanuele Marzetti; Francesco Landi; Leocadio Rodriguez-Mañas (Elsevier, 2024)
Background: An age-dependent normative values of calf circumference (CC) has been recently proposed as an accessible proxy for muscle mass. However, its usefulness to estimate sarcopenia has not been assessed. The objectives of the present study were to determine if the substitution of the classical way to assess muscle mass by these values have enough diagnostic accuracy and prognostic value among older adults living in the community. Methods: Data from the Toledo Study of Healthy Ageing (TSHA) were used. CC was measured using an anthropometric tape. We used two age-groups CC cut-off points: the TSHA CC median and the one proposed in the Longevity Check-up 7+ (Lookup 7+) project. Sarcopenia was defined based on the European Working Group on Sarcopenia in Older People (EWGSOP2), the Foundation for the National Institutes of Health (FNIH), and FNIH criteria standardized for our population (sFNIH). Frailty (according to the Frailty Phenotype and the Frailty Trait Scale-5) and disability (Katz index) were assessed at baseline and follow-up. Mortality and first hospitalization were also recorded. Logistic (incident frailty and worsening disability) and Cox (mortality and hospitalization) regressions were performed. Diagnostic accuracy was assessed through Kappa index, AUCs, positive and negative predictive values. Predictive ability was assessed through AUCs and integrated AUCs (IAUCs). Results: 1531 participants (74.8 ± 5.8 years; 45.6% men) were included in the analysis. Prevalence rates of sarcopenia were 22.7% (sFNIH), 15.0% (FNIH), and 13.9% (EWGSOP2). Using TSHA-based cut-points of CC, the prevalence of sarcopenia was 16.8% (sFNIH), 11.0% (FNIH), and 11.5% (EWGSOP2). According to LC7+-based CC cut-off points, sarcopenia prevalence was 17.6% (sFNIH), 11.9% (FNIH), and 12.4% (EWGSOP2). CC cut-off points showed low-to-moderate agreement (Kappa Index values between 0.49 and 0.69) with appendicular lean mass for the evaluation of sarcopenia. Sarcopenia identified by Lookup 7+ and TSHA CC cut-off points was associated with the adverse events examined, with similar AUCs and IAUCs than original sarcopenia definitions, and were lost after adjustment by baseline frailty, except when the original EWGSOP2 definition was used. Conclusions: Using normalized values of CC as a criteria of muscle mass shows moderate agreement with classical criteria for diagnosing sarcopenia and offer similar predictive value in community-dwelling older adults.